Wood harvesting - Dykstra, D.P.; Poschen, P. (1998)
Wood harvesting is the preparation of logs in a forest or tree plantation according to the requirements of a user, and delivery of logs to a consumer. It includes the cutting of trees, their conversion into logs, extraction and long distance transport to a consumer or processing plant. This article describes the sequence of wood harvesting operations, common methods, equipment and hazards, including felling and extraction preparation, extraction and log making and loading, and standards and regulations.